1999
DOI: 10.1002/(sici)1097-0185(19991201)256:4<433::aid-ar10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Course and composition of the nerves that supply the mandibular teeth of the rat

Abstract: The rodent dentition has become an important model for investigations of interactions between dental tissues and peripheral neurons. Although experimental nerve injury has been widely used for such studies, there is uncertainty about the courses of nerve fibers supplying the mandibular teeth. In order to clarify this, we used a mixture of monoclonal antibodies against neurofilament proteins to enhance demonstration of nerve fibers so that small nerves could be readily traced in serial frozen sections of mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 65 publications
0
15
1
1
Order By: Relevance
“…Several literatures suggested that over 60% of axons of inferior alveolar nerve neurons were myelinated [24-27], which showed discrepancyto our data in whichonly 25.7% were myelinated. In addition, more recent study reported that most of parental axons traced with horseradish peroxidase placed in upper molars of rats were myelinated [28].…”
Section: Discussioncontrasting
confidence: 99%
“…Several literatures suggested that over 60% of axons of inferior alveolar nerve neurons were myelinated [24-27], which showed discrepancyto our data in whichonly 25.7% were myelinated. In addition, more recent study reported that most of parental axons traced with horseradish peroxidase placed in upper molars of rats were myelinated [28].…”
Section: Discussioncontrasting
confidence: 99%
“…However, photographic analysis can only provide cross‐sectional data. The plane formed by the mental and the mandibular foramens was chosen as a reference plane (14), since the endoskeleton of the rat mandible, including these two anatomical features, has been found to be the most stable structure during development (19).…”
Section: Discussionmentioning
confidence: 99%
“…1, the area of the external surface of the hemi-mandible, including the condylar process, excluding the teeth; 2, the area of the condylar process, delimited by the condylar tangent (tangent to both upper and posterior mandibular notches); 3, the angle formed by the perpendicular from the most posterior and superior part of the condyle to the condylar tangent and the reference plane; 4, the angle formed by the axis of the incisor alveolar process and the reference plane (incisor alveolar axis: a line from the midpoint between the upper and lower aspect of the incisor alveolar crest to the midpoint between the deepest part of the incisor alveolar curvature and the edge of the digastric fossa; 5, the angle formed by the lower border of the mandible and the reference plane; 6, the angle formed by the occlusal plane and the reference plane; 7, the maximal distance of the condyle from the condylar tangent; 8, the maximal distance between the mental foramen and the condyle; 9, the maximal distance between the mental foramen and the coronoid process; 10, the maximal distance between the mental foramen and the angular process; 11, the distance between the condylar tangent points; 12, the maximal vertical distance of the coronoid process from the reference plane; 13, the maximal vertical distance of the angular process from the reference plane; 14, the distance between the reference plane and the deepest point of the alveolar crest of the third molar; 15, the distance between the reference plane and the deepest point of the alveolar crest of the first molar; 16, the distance between the reference plane and the mesial cusp of the third molar; 17, the distance between the reference plane and the middle cusp of the first molar. ular foramens was chosen as a reference plane (14), since the endoskeleton of the rat mandible, including these two anatomical features, has been found to be the most stable structure during development (19).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the anatomical relation between developing teeth and trigeminal fibers has been extensively studied in the past (Byers, 1984;Luukko, 1997;Naftel et al, 1999), our knowledge of how the dental pulp becomes innervated is still only fragmentary. Trigeminal axons are present before any structural signs of tooth formation are detectable.…”
Section: Introductionmentioning
confidence: 99%